2015
DOI: 10.1159/000369703
|View full text |Cite
|
Sign up to set email alerts
|

Matrine Inhibits Mouse Sperm Function by Reducing Sperm [Ca2+]i and Phospho-ERK1/2

Abstract: Background: Matrine is a bioactive alkaloid that has a variety of pharmacological effects and is widely used in Chinese medicine. However, its effects on male reproduction are not well known. In this study, we aimed to investigate the in vitro toxicity of matrine on mature mouse sperm. Methods: Mouse cauda epididymal sperm were exposed to matrine (10-200 µM) in vitro. The viability, motility, capacitation, acrosome reaction and fertilization ability of the mouse sperm were examined. Furthermore, the intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…Further studies are needed on the mechanism involved. In addition, as summarized in Tables 1 and 2, the toxic doses of MT significantly affected the mitochondrial apoptotic pathway, Nrf2 pathway and In vivo (Luo et al, 2015;Luo et al 2016) FIGURE 3 | Toxicity and mechanism of Matrine. Zhang et al, 2008 Rat Oral MT, 40 mg/kg C max and T max of approximately 3900 ng/ml and 50 min, respectively Wu et al, 2003 Rat Intravenous MT, 15 mg/kg Rapidly distributed to various tissues and organs, such as liver, spleen and kidney.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are needed on the mechanism involved. In addition, as summarized in Tables 1 and 2, the toxic doses of MT significantly affected the mitochondrial apoptotic pathway, Nrf2 pathway and In vivo (Luo et al, 2015;Luo et al 2016) FIGURE 3 | Toxicity and mechanism of Matrine. Zhang et al, 2008 Rat Oral MT, 40 mg/kg C max and T max of approximately 3900 ng/ml and 50 min, respectively Wu et al, 2003 Rat Intravenous MT, 15 mg/kg Rapidly distributed to various tissues and organs, such as liver, spleen and kidney.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Investigation of the relationship between MTinduced neurotoxicity and oxidative stress in PC12 cells indicated that MT induced high level of oxidative stress after treatment with graded concentrations of MT (2-8 mM) for 48 h, resulting in a reduction of SOD and an increase in ROS and MDA, as well as activation of the mitochondria-dependent apoptotic pathway (Shen et al, 2017). In terms of reproductive toxicity, Luo et al (2015) was the first to show that MT (100-200 µM) suppressed mouse sperm function by reducing sperm [Ca 2+ ] i and inhibiting the phosphorylation of ERK1/2. Moreover, further studies indicated that MT (10 ang50 mg/kg/day for 30 days) inhibited mouse sperm function through the [Ca 2+ ] i -related mechanism via the CatSper channel, which is the main channel for controlling extracellular Ca 2+ influx in mouse sperm (Luo et al, 2015;Luo et al, 2016).…”
Section: Toxicologymentioning
confidence: 99%
“…The normal semen samples were treated with the anti-SMS2 antibody in a 5% CO 2 incubator for 1 h at 37 °C, and the control groups were treated with the IgG antibody. For each group, more than 200 sperm cells were counted [ 43 ]. Then, these treated cells were used to measure the motility and penetration into methylcellulose.…”
Section: Methodsmentioning
confidence: 99%
“…Matrine and sophoridine are quinolizidine alkaloids isolated from traditional Chinese medicine such as Sophora flavescens, Sophora subprostrata, or Sophora alopecuroides, which are tetracyclic quinolizine compounds with a molecular skeleton and can be regarded as a combination of two quinolizine rings [ 19 , 20 ]. In recent years, it has been discovered that the alkaloids of S. flavescens exhibit anti-arrhythmic, anti-inflammatory, anti-fibrosis, anti-tumor, and numerous other significant pharmacological activities, and various formulations have been widely used in clinical practice [ 21 , 22 , 23 , 24 ]. Therefore, in the present work, we used matrine and sophoridine as target drug molecule probes to study the switching properties of the binary carboxylated multi-walled carbon nanotubes/poly( N , N -diethylacrylamide) (c-MWCNTs/PDEA) film system.…”
Section: Introductionmentioning
confidence: 99%